Elite Formation, Power and Space in Contemporary London. (September 2017) - Atkinson, Rowland; Parker, Simon; Burrows, Roger
In this article we examine elite formation in relation to money power within the city of London. Our primary aim is to consider the impact of the massive concentration of such power upon the city's political life, municipal and shared resources and social equity. We argue that objectives of city success have come to be identified and aligned with the presence of wealth elites while wider goals, of access to essential resources for citizens, have withered. A diverse national and global wealth-elite is drawn to a city with an almost unique cultural infrastructure, fiscal regime and ushering butler class of politicians. We consider how London is being made for money and the monied – in physical, political and cultural terms. We conclude that the conceptualization of elites as wealth and social power formations operating within urban spatial arenas is important for capturing the nature of new social divisions and changes.